A discrete event model for real time system simulation - Paez, Francisco Ezequiel (2012)
In this work we present a discrete event model to design and implement a real time system simulator. This kind of software is useful to verify and evaluate algorithms and models, and to compute performance metrics. The discrete event model fits perfectly with discrete dynamical system such as Real Time Systems. The event graph technique is then used as the modeling tool.